Adaptation of Running Biomechanics to Repeated Barefoot Running: A Randomized Controlled Study. Issue 8 (July 2019) - Hollander, Karsten; Liebl, Dominik; Meining, Stephanie; Mattes, Klaus; Willwacher, Steffen; Zech, Astrid
Background: Previous studies have shown that changing acutely from shod to barefoot running induces several changes to running biomechanics, such as altered ankle kinematics, reduced ground-reaction forces, and reduced loading rates. However, uncertainty exists whether these effects still exist after a short period of barefoot running habituation. Purpose/Hypothesis: The purpose was to investigate the effects of a habituation to barefoot versus shod running on running biomechanics. It was hypothesized that a habituation to barefoot running would induce different adaptations of running kinetics and kinematics as compared with a habituation to cushioned footwear running or no habituation. Study Design: Controlled laboratory study. Methods: Young, physically active adults without experience in barefoot running were randomly allocated to a barefoot habituation group, a cushioned footwear group, or a passive control group. The 8-week intervention in the barefoot and footwear groups consisted of 15 minutes of treadmill running at 70% of VO2 max (maximal oxygen consumption) velocity per weekly session in the allocated footwear. Before and after the intervention period, a 3-dimensional biomechanical analysis for barefoot and shod running was conducted on an instrumented treadmill. The passive control group did not receive any intervention but was also tested prior to and after 8 weeks. Pre- to posttest changes in kinematics, kinetics, and spatiotemporal parameters were then analyzed with a mixed effects model. Results: Of the 60 included participants (51.7% female; mean ± SD age, 25.4 ± 3.3 years; body mass index, 22.6 ± 2.1 kg·m -2 ), 53 completed the study (19 in the barefoot habituation group, 18 in the shod habituation group, and 16 in the passive control group). Acutely, running barefoot versus shod influenced foot strike index and ankle, foot, and knee angles at ground contact ( P < .001), as well as vertical average loading rate ( P = .003), peak force ( P < .001), contact time ( P < .001), flight time ( P < .001), step length ( P < .001), and cadence ( P < .001). No differences were found for average force ( P = .391). After the barefoot habituation period, participants exhibited more anterior foot placement ( P = .006) when running barefoot, while no changes were observed in the footwear condition. Furthermore, barefoot habituation increased the vertical average loading rates in both conditions (barefoot, P = .01; shod, P = .003) and average vertical ground-reaction forces for shod running ( P = .039). All other outcomes (ankle, foot, and knee angles at ground contact and flight time, contact time, cadence, and peak forces) did not change significantly after the 8-week habituation. Conclusion: Changing acutely from shod to barefoot running in a habitually shod population increased the foot strike index and reduced ground-reaction force and loading rates. After the habituation to barefoot running, the foot strike index was further increased, while the force and average loading rates also increased as compared with the acute barefoot running situation. The increased average loading rate is contradictory to other studies on acute adaptations of barefoot running. Clinical Relevance: A habituation to barefoot running led to increased vertical average loading rates. This finding was unexpected and questions the generalizability of acute adaptations to long-term barefoot running. Sports medicine professionals should consider these adaptations in their recommendations regarding barefoot running as a possible measure for running injury prevention. Registration: DRKS00011073 (German Clinical Trial Register).